Characteristics of Kiblat Films and The Application of Article 156a Kuhp To Blasphemy - Nabila Dian; Mochamad Mansur (Journal Equity of Law and Governance, 2025)
This research examines the characteristics of the ‘Kiblat’ film that caused controversy and the implementation of article 156a KUHP to blasphemy cases. This research aims to clarify whether the film ‘Kiblat’ is blasphemy or freedom of expression, as well as ensure consistent legal protection for religious people, enforce the law against blasphemy, and prevent potential social conflicts. This study uses a type of normative legal research.  The results of this study show that the ‘Kiblat’ film is considered to insult Islam by displaying religious symbols inappropriately. This raises concerns about the negative impact on religious harmony and violates Article 156a KUHP regarding blasphemy. Laws such as the ITE Law also function to regulate the dissemination of content that can cause hatred, especially related to religion. The government has an important role to play maintaining a balance between freedom of expression and respect for religious values.